True lab-in-a-syringe technology for bioassays - Hárendarčíková, Lenka; Baron, Daniel; Šebestová, Andrea; Rozsypal, Jan; Petr, Jan (Talanta, 2017)
In our work, we introduced a novel concept of the lab-in-a-syringe tests. We solved the problem of detection in already published LIS tests by putting all the reaction and detection pads directly into the syringe barrel. We also used more layers to make the results visible for users. Two detection layouts: (i) with using rounded pads-based detection, and (ii) with using rectangular detection pads, were studied. As the proof of concept, we studied the determination of Ni(II) using dimethylglyoxime as the reagent and blocking of the interference of Fe(II). The calibrations for Ni(II) at the optimal conditions has excellent R2 of 0.998 with production costs of 0.2 USD per one test.
Keywords: biotest; Lateral-flow assay; Lab-in-a-syringe; Equipment Design; injekční stříkačky; Sensing; design vybavení; Syringes; Low-cost microfluidics; Biological Assay